1985
DOI: 10.1002/elps.1150060809
|View full text |Cite
|
Sign up to set email alerts
|

Gene frequency distribution of the B subunit of factor XIII (F XIIIB) in Minnesota Whites, Blacks and Amerindians

Abstract: Serum specimens from local Whites, Blacks and Amerindians were phenotyped for the B subunit of Factor XIII. Isoelectric focusing of desialylated samples on agarose gels at a pH 4–7 gradient followed by an immunoblotting technique was used for band identification. Gene frequencies for the three common alleles in Whites, F XIII*1, F XIIIB*2 and F XIIIB*3 were 0.776, 0.088 and 0.136, respectively, and were consistent with reports on this genetic marker system in European Whites. The Blacks and Amerindians were cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The population studied is in genetic equilibrium assuming the HardyWeinberg hypothesis. When compared with those obtained in various other populations [1][2][3][4][5][6][9][10][11][12], our results in Libyans showed marked differences in the frequencies of the three common alleles FXIIIB*I, FXIIIB*2, FXIIIB*3 and the occurrence of a fourth common allele, FXIIIB*6. Further investigations in other Arab populations will clarify whether the FXIIIB*6 allele is specific for Libyans or a characteristic marker for Arabs.…”
Section: Immunoblottingmentioning
confidence: 71%
“…The population studied is in genetic equilibrium assuming the HardyWeinberg hypothesis. When compared with those obtained in various other populations [1][2][3][4][5][6][9][10][11][12], our results in Libyans showed marked differences in the frequencies of the three common alleles FXIIIB*I, FXIIIB*2, FXIIIB*3 and the occurrence of a fourth common allele, FXIIIB*6. Further investigations in other Arab populations will clarify whether the FXIIIB*6 allele is specific for Libyans or a characteristic marker for Arabs.…”
Section: Immunoblottingmentioning
confidence: 71%
“…F13B*2 is a good marker of African ancestry (56-63% among Blacks; lower than 15% elsewhere), and F13B*3 could be considered a Mongoloid marker, with a prevalence above 67% among people of Asian descent and lower among the others. Miller et al (1985) and Kamboh and Ferrel (1986) reported studies among three North and one Central American Indian populations, as well as in two Eskimo groups. The Mongoloid pattern outlined above is present among them, but none showed such a low prevalence of F13B*l and high of F13B*3 as the populations studied by us.…”
Section: Resultsmentioning
confidence: 98%